Point-of-care ultrasound techniques for the small animal practitioner - Lisciandro, Gregory R. (Hoboken, New Jersey Wiley-Blackwell, 2020)
This book offers a thorough revision and update to the first landmark book that presented a standardized approach to focused point-of-care ultrasound exams of the abdomen, thorax, musculoskeletal and eye in veterinary practice. Now incorporating new applications for focused ultrasound exams and additional species, this Second Edition continues to be a state-of-the-art reference for using abbreviated ultrasound exams in clinical practice. A companion website features supplementary video clips of these point-of-care techniques depicting actual ultrasound exams for comparison and comprehension. New chapters in Point-of-Care Ultrasound Techniques for the Small Animal Practitioner, Second Edition cover ultrasound-guided nerve blocks, musculoskeletal, brain imaging, and applications of focused ultrasound techniques in cats, exotics and marine mammals--making it an essential purchase for veterinarians wanting to incorporate point-of-care ultrasound techniques into their veterinary practices. The second edition of Point-of-Care Ultrasound Techniques for the Small Animal Practitioner is an excellent resource for veterinary practitioners, ranging from the general practitioner to nearly all clinical specialists, including internal medicine, oncology, cardiology, emergency and critical care, anesthesiology, ophthalmology, exotics, and zoo medicine specialists, and veterinary students.
Preceded by Focused ultrasound techniques for the small animal practitioner/ edited by Gregory R. Lisciandro. 2014.
Includes bibliographical references and index.
Keywords: Ultrasonography -- veterinary; Pets; Point-of-Care Systems; Animal Diseases -- diagnostic imaging